Water Mobile Phase HPLC Determination of Acetamiprid and Its Metabolite, IM-2-1 - N. Furusawa (Challenges and Advances in Chemical Science Vol. 9, 2022)
This chapter presents a harmless HPLC technique for detecting acetamiprid (ATP) and its metabolite, IM-2-1 (IM2), using an isocratic 100 % water mobile phase. Chromatographic separations were carried out on an Inertsil® WP300 C4 using water as the mobile phase and a photodiode-array detector (PDA). The total run time was < 7 min: the retention times for ATP and IM2 were 5.75 and 6.49 min, respectively. The linearity and system suitability were well within the international acceptance criteria. The detection limits were 0.013 \(μ\)g/mL for ATP and 0.006 \(μ\)g/mL for IM2, respectively. A safe HPLC method for simultaneously detecting ATP and IM2 was developed, and it may be applied to the quantification of animal-derived foods in the future.